How to Prevent Foreclosure on Your Home - Michael Gutter; Virginia Peart (EDIS, 2008)
Revised! FCS-3227, a 3-page fact sheet by Michael Gutter and Virginia Peart, explains what foreclosure is, when it can occur, and how to avoid the serious damage it can cause to your financial status and credit rating. Includes suggestions on working with lenders. Revised to reflect new information and resources. Published by the UF Department of Family, Youth and Community Sciences, December 2007.